Analysis of customers' satisfaction with baby products: The moderating role of brand image. (July 2023) - Nilashi, Mehrbakhsh; Abumalloh, Rabab Ali; Samad, Sarminah; Alrizq, Mesfer; Alyami, Sultan; Alghamdi, Abdullah
Abstract: The previous experience of customers is assessed by textual reviews and ratings to reflect their levels of satisfaction with the service or product. Online reviews and ratings have played a vital role to assess the performance of the services or the quality of goods. This research explores customers' levels of satisfaction with baby products on Amazon.com through text mining and survey-based methodologies. The moderating role of a brand image is also investigated on the relationship between customers' satisfaction and recommendations to others. Two sources of data were utilized, online reviews from the Amazon portal and responses of the participants on a large-scale survey. The research model is developed based on the factors that were extracted from the text mining approach. Following that, a questionnaire was distributed and the collected data were inspected using Partial Least Squares Structural Equations Modeling (PLS-SEM). The findings revealed that several dimensions have an influential effect on customers' experiences with baby products, among which are comfortableness, material quality, easy use, easy return, design, price, packaging, and size information. In addition, the moderating influence of the brand image on the hypothesis between customers' satisfaction and recommendations to others was significant. By deploying the two-phase methodology, baby product vendors can understand the influential variables in customers' experiences and their impacts on customers' satisfaction more accurately.